Practical considerations in the design & selection of windows for a Filipino house - Aguila, Edgardo A. 1950- (1986)
Windows is an essential element in any architectural design. Throughout the history of man, windows have been part of man's daily activities within his dwelling. The need for windows resulted in the development of windows in terms of style/teratment, and window galzing materials. Basically due to this development, these resulted to an evolutionary process of window design being used in our country, or generally for a Filipino house. With the state of economic condition facing the country and the laaging state of the building industry, there should be a system devloped to achieve cost effectiveness in the design of windows for a Filipino house. Prices for construction materials are escalating. In general, building components are expensive. There seems to be a lot of wastage in the use of materials via the carftman approach of building. There is a certain of a regulative body to standardize building components, kniwn as the Product Standards Agency. A practical solution for window design can be solved through the industrialization of building components, i.e. the standardization of window dimensions. That the basis for standardization of windo dimensions is the result of considerable studies involving the establishment of criteria required for proper window design. Objectives of the thesis: To determine the different classification of window types and its function, and the different classification of window materials and galzing materials; to determine the different criteria needed for effective window design; to establish importance of and the need for stnadardizing window dimension as part of the industrialization of building componenets; to provide practical considerations in the design and selection of windows for a Filipino house. Strategies: Presentation of a thorough study on the different classification of window types and its functions, and the different classicification of window materials and glazing materials; expound on the different criteria established for proper window design. Presentation of an evaluation-study of the different window types based on different criteria established for effective window design; presentation of an evaluation-study of the different window types based on different criteria established for effective window design; presentation of evaluation-study of the different window types and its application to the established criteria as applied to the author's house; presentation of a general analysis on the cost effectiveness of standardization window dimension.